Spectroscopic analysis of base solutions - Wong, Lydia Qing Yi (2019)
Through the analysis of the Infrared spectrum of NaOH, the respective lengthening and shortening of H-O and O:H bonds due to the Coulomb repulsion between electron lone pairs on Oxygen will be studied in this report. From the IR spectrum obtained from the samples, peaks will be observed to deduce the possible molecular vibrations occurring at the specific frequencies and the compression or elongation of the H-O bonds will be inferred accordingly. As the structure upon NaOH hydration can be derived from the ideal tetrahedral structure of water with the replacement of the central charge, water will be used as a reference and the understanding of NaOH hydration will be largely based on the effects of mechanical compression on water.